Offering of naivedya to the goddess - Mumbai Archive Project Team (Jio Institute, 2024)
Sixteen special food items are prepared and offered to the Goddess as naivedya (sacred food offerings). These include sweet items like modak (Lord Ganesha’s favourite sweet) and kheer (sweet pudding). It is believed that the deity partakes in the essence of the food, which is then distributed to the devotees as prasad (blessed food).